2018
DOI: 10.3847/1538-4357/aaeff0
|View full text |Cite
|
Sign up to set email alerts
|

Emission Signatures from Sub-parsec Binary Supermassive Black Holes. II. Effect of Accretion Disk Wind on Broad Emission Lines

Abstract: We present an improved semi-analytic model for calculation of the broad optical emission-line signatures from sub-parsec supermassive black hole binaries (SBHBs) in circumbinary disks. The secondgeneration model improves upon the treatment of radiative transfer by taking into account the effect of the radiation driven accretion disk wind on the properties of the emission-line profiles. Analysis of 42.5 million modeled emission-line profiles shows that correlations between the profile properties and SBHB parame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…F I G U R E 2 H𝛽 line profile emitted from six different positions during one full rotation of the supermassive binary black hole system with a total mass of ∼ 10 6 M ⊙ . The initial phase was taken when binaries are in an aphelion position, and time elapsed is indicated in the upper corner of each plot of which two are connected with the moving SMBHs and one is circumbinary and stationary (like in the Nguyen & Bogdanovi ć 2016; Nguyen et al 2019;Nguyen et al 2020a;Nguyen et al 2020b). In addition, in difference with these models, in the PoSKI model, we consider that the size of the moving BLRs around each SMBH is defined by their Roche lobes (affected by relativistic beaming) and that the stationary cBLR dimension depends on the total disc continuum luminosity of the system.…”
Section: Modelmentioning
confidence: 99%
“…F I G U R E 2 H𝛽 line profile emitted from six different positions during one full rotation of the supermassive binary black hole system with a total mass of ∼ 10 6 M ⊙ . The initial phase was taken when binaries are in an aphelion position, and time elapsed is indicated in the upper corner of each plot of which two are connected with the moving SMBHs and one is circumbinary and stationary (like in the Nguyen & Bogdanovi ć 2016; Nguyen et al 2019;Nguyen et al 2020a;Nguyen et al 2020b). In addition, in difference with these models, in the PoSKI model, we consider that the size of the moving BLRs around each SMBH is defined by their Roche lobes (affected by relativistic beaming) and that the stationary cBLR dimension depends on the total disc continuum luminosity of the system.…”
Section: Modelmentioning
confidence: 99%
“…The PoSKI model (Popović et al, 2021) belongs to a group of models (se e.q. D'Orazio, Haiman, & Schiminovich, 2015;Nguyen et al, 2019;Nguyen, Bogdanović, et al, 2020;Nguyen, Bogdanovic, et al, 2020) that predicts periodicities in the emission line/continuum light curves and broad line parameters of SMBBHs. There are significant similarities between the PoSKI and models implemented in mentioned papers.…”
Section: Modelmentioning
confidence: 99%
“…There are significant similarities between the PoSKI and models implemented in mentioned papers. For example, our model uses the relativistic beaming effect proposed by D' Orazio et al (2015), but in addition include three BLRs, of which two are connected with the moving SMBHs and one is circumbinary and stationary (like in the Nguyen & Bogdanović, 2016;Nguyen et al, 2019;Nguyen, Bogdanović, et al, 2020;Nguyen, Bogdanovic, et al, 2020). In addition, in difference with these models, in the PoSKI model we consider that the size of the moving BLRs around each SMBH are defined by their Roche lobes (affected by relativistic beaming) and that the stationary cBLR dimension depends on the total disc continuum luminosity of the system.…”
Section: Modelmentioning
confidence: 99%
“…Some of the line profiles generated were highly complex and time variable, including multiple peaks, but they were also highly dependent on the semimajor axis of the binary as well as on the alignment between the mini disks and the observer. Further work by Nguyen et al (2019) revealed that including the effects of accretion disk winds eliminated the more complex line profiles. This recent work therefore argued that emission-line profiles on their own cannot be used to confirm an SMBH binary.…”
Section: Predicted Observational Signatures Of Binary Smbhsmentioning
confidence: 99%